Impact of Spanish gambling regulations on online gambling behavior and marketing strategies - Gema Aonso-Diego; Ángel García-Pérez; Andrea Krotter (Harm Reduction Journal)
Abstract Background A large body of research has pointed out that advertising has an impact on gambling behavior. However, little is known about how actual gambling marketing regulations impact online gambling behavior and marketing expenditure. Recently, a Spanish law—the Royal Decree 958/2020—came into force, which, in general terms, limits the marketing of gambling products. The current study aimed to examine the effect of the Spanish Royal Decree 958/2020 on gambling behavior (i.e., new accounts, active accounts, deposits, and total money bet) and marketing expenditure (i.e., advertising, bonuses, affiliation, and sponsorship) based on data from the Directorate General for Regulation of Gambling. Methods We used Seasonal Autoregressive Integrated Moving Average (SARIMA) models to examine the impact of the implementation of Royal Decree 958/2020 on both online gambling behavior and marketing expenditure. Results The entry into force of the Spanish Royal Decree (applied between November 2020 and August 2021) led to a permanent decrease in gambling behavior, in particular new accounts (-263k; p = .003) and total money bet (-€216M; p = .034). Additionally, regulatory measures had an impact on marketing strategies, specifically, reducing money earmarked for advertising (-€20M; p = .004), bonuses (-€2.6M; p = .048), and sponsorship (-€5.3M; p < .001). Conclusion These findings demonstrate that regulatory measures aimed at limiting gambling advertising, bonuses, and sponsorships impact new accounts (i.e., new gamblers) and total money gambled, but hardly active accounts (i.e., regular gamblers). This study can serve as a model for countries where gambling advertisements have not yet been regulated.